Antiviral effects of autologous CD4 T cells genetically modified with a conditionally replicating lentiviral vector expressing long antisense to HIV - Tebas, Pablo; Stein, David; Binder-Scholl, Gwendolyn; Mukherjee, Rithun; Brady, Troy; Rebello, Tessio; Humeau, Laurent; Kalos, Michael; Papasavvas, Emmanouil; Montaner, Luis J.; Schullery, Daniel; Shaheen, Farida; et al. (Blood, 2013)
We report the safety and tolerability of 87 infusions of lentiviral vector–modified autologous CD4 T cells (VRX496-T; trade name, Lexgenleucel-T) in 17 HIV patients with well-controlled viremia. Antiviral effects were studied during analytic treatment interruption in a subset of 13 patients. VRX496-T was associated with a decrease in viral load set points in 6 of 8 subjects (P = .08). In addition, A → G transitions were enriched in HIV sequences after infusion, which is consistent with a model in which transduced CD4 T cells exert antisense-mediated genetic pressure on HIV during infection. Engraftment of vector-modified CD4 T cells was measured in gut-associated lymphoid tissue and was correlated with engraftment in blood. The engraftment half-life in the blood was approximately 5 weeks, with stable persistence in some patients for up to 5 years. Conditional replication of VRX496 was detected periodically through 1 year after infusion. No evidence of clonal selection of lentiviral vector–transduced T cells or integration enrichment near oncogenes was detected. This is the first demonstration that gene-modified cells can exert genetic pressure on HIV. We conclude that gene-modified T cells have the potential to decrease the fitness of HIV-1 and conditionally replicative lentiviral vectors have a promising safety profile in T cells. This study is registered at www.clinicaltrials.gov as number NCT00295477. •Adoptive transfer of autologous lentiviral-engineered T cells expressing an antisense is safe in chronic HIV infection.•Conditionally replicating lentiviral vector was associated with antiviral effects in patients as assessed by viral evolution and viral load.